DNA ligase IV guides end-processing choice during nonhomologous end joining - Conlin, Michael P. (Cell Rep, 2017)
Nonhomologous end joining (NHEJ) must adapt to diverse end structures during repair of chromosome breaks. Here we investigate the mechanistic basis for this flexibility. DNA ends are aligned in a paired-end complex (PEC) by Ku, XLF, XRCC4, and DNA ligase IV (LIG4); we show by single-molecule analysis how terminal mispairs lead to mobilization of ends within PECs, and consequent sampling of more end-alignment configurations. This remodeling is essential for direct ligation of damaged and mispaired ends during cellular NHEJ, since remodeling and ligation of such ends both require a LIG4-specific structural motif, insert1. Insert1 is also required for PEC remodeling that enables nucleolytic processing when end structures block direct ligation. Accordingly, cells expressing LIG4 lacking insert1 are sensitive to ionizing radiation. Cellular NHEJ of diverse ends thus identifies the steps necessary for repair through LIG4-mediated sensing of differences in end structure, and consequent dynamic remodeling of aligned ends.